THE ESSENCE OF INNOVATIVE MARKETING AND MARKETING SYSTEMS: MODERN CONCEPTS AND THEIR IMPACT ON ENTERPRISE DEVELOPMENT - SHESTAKOVSKA, Tetiana; SHEVCHENKO, Oleh; SEMCHENKO-KOVALCHUK, Olena; NIKOLAYENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals the essence of innovative marketing as a complex system of strategic measures that ensure the effective promotion of new products and technologies on the market. It is determined that innovative marketing encompasses market analysis, adaptation to the competitive environment, and the implementation of digital tools in the enterprise’s communication policy. It is stated that the key aspects of modern innovative marketing include the use of Big Data, artificial intelligence, and digital platforms, which enhance feedback with target segments. The study emphasizes the expediency of considering innovative marketing as a component of innovation activity focused on the commercialization of scientific and technological solutions. It has been found that the effectiveness of such approaches is manifested in profit maximization through meeting actual consumer needs. The paper underlines that innovations serve as a factor of long-term development and enterprise competitiveness in a global market environment. It is specified that strategic marketing decisions must take into account shifts in demand structure, behavioral transformations, and technological dynamics. It is noted that innovative marketing is a tool for proactively shaping market trends. The role of top management in implementing innovative marketing approaches is substantiated. The authors argue that, in accordance with international standards, the success of innovative products depends on their ability to gain a foothold in the market. It is established that business digitalization requires the use of CRM systems, omnichannel promotion, and MarTech tools. It is noted that an effective innovative marketing strategy involves coordinated product planning, distribution channels, pricing policy, and interdepartmental cooperation. The article outlines that successful functioning under conditions of digital transformation is ensured by flexibility, adaptability, and the integration of modern tools into marketing management.